Learning cultures and cultural learning in high-performance sport: opportunities for sport pedagogues - Barker-Ruchti, N.; Barker, D.; Rynne, S. B.; Lee, J. (Physical Education and Sport Pedagogy, 2016)
High-performance sports provide athletes with a variety of learning experiences. Because athletes invest significant time and energy in training and competition over relatively long periods of time and because sport assumes high levels of significance to athletes, learning can involve intense and long-lasting changes that have consequences within and beyond sport (Barker et al. 2014; Barker-Ruchti et al. 2012). Despite the centrality of learning in high-performance sport, scholars have given this topic little attention. While there are exceptions (e.g. Gearity 2012; Light 2010; McMahon and Penney 2013; Rynne, Mallett, and Tinning 2010), many aspects of learning in highperformance sport remain unchartered. The limited body of literature on learning in high-performance sport may surprise since this topic has received considerable attention in physical education, in relation to both phys- ical education pupils (e.g. Quennerstedt et al. 2014; Quennerstedt, Ohman, and Ohman, 2011) and physical education teachers (e.g. Armour, Makopoulou, and Chambers 2012; Keay 2005, 2006; Makopoulou and Armour 2011; Sirna, Tinning, and Rossi 2008). Using socio-cultural perspectives of learning, this literature demonstrates that learning occurs continuously and regardless of, for instance, teaching method and age/career stage, but is influenced by reflexive interactions between socio-cultural, structural and situational factors and individual agency. In so doing, this existing literature points to the complex and relational nature of learning.